Scientific American. – 1870. – Vol. 22, № 6 - б/а (New York. Munn & Company, 1870)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
З фонду Центральної наукової бібліотеки Харківського національного університету імені В.Н. Каразіна.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; February 5, 1870